2010
DOI: 10.1002/hup.1104
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of long‐acting injectable risperidone in patients with schizophrenia spectrum disorders: A 6‐month open‐label trial in Asian patients

Abstract: The study aimed to evaluate the efficacy of long-acting injectable risperidone (LAR) in Asian patients with schizophrenia spectrum disorders. Twenty-five patients enrolled in this 6-month open labelled study. They were switched from their current antipsychotic to LAR without a prior oral risperidone run-in phase. Efficacy was assessed by the positive and negative syndrome scale (PANSS) and clinical global impression (CGI) scales. Extra-pyramidal side effects (EPSE) was assessed using the Simpson Angus Scale (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Three studies assessed conventional LAIAs, two studies included several LAIAs, nine studies involved long‐acting risperidone injection (RLAI), one study assessed olanzapine long‐acting injection (LAI) and two studies involved paliperidone palmitate (PP). Nine of the 17 included studies reported data on relapse, the primary outcome measure …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies assessed conventional LAIAs, two studies included several LAIAs, nine studies involved long‐acting risperidone injection (RLAI), one study assessed olanzapine long‐acting injection (LAI) and two studies involved paliperidone palmitate (PP). Nine of the 17 included studies reported data on relapse, the primary outcome measure …”
Section: Resultsmentioning
confidence: 99%
“…There was a significant increase in body mass index ( P < 0.001) as well as increase in plasma cholesterol and fasting glucose. The authors concluded that RLAI was effective in first‐episode patients, and that it is not necessary to have a run‐in phase with oral risperidone before switching to RLAI, but were concerned about the observed metabolic side‐effects …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From a clinical perspective, PANSS, age and gender are the most commonly used data to measure symptoms severity and characteristics of patients with schizophrenia either in trials or intervention programs in Singapore. For example, in Singapore’s Early Psychosis Intervention Programme’s (EPIP) [ 33 ] long-acting injectable risperidone (LAR) trial [ 34 ], information on symptom severity was routinely captured by case managers to monitor patients as well as to assess the efficacy of the antipsychotic medication but the trial lacked a cost-effectiveness component. The availability of this algorithm will make cost–utility analysis among patients with schizophrenia who are monitored only for symptom severity possible in future trials and program evaluation.…”
Section: Discussionmentioning
confidence: 99%